The Analysis of Main Character’s Self-Deception and Hypocrisy in the Film Boss Baby - Kholidatul Jannah; Dian Maya Kurnia (Pioneer: Journal of Language and Literature, 2019)
Self-deception was deceivers make themselves to believe something which they knew it was false, while hypocrisy was the practice of pretending to be different from what one really. Self-deception and hypocrisy were the core of this research in the filmBoss Baby. There were four research problems in this research; what were self-deception found in thefilmBoss Baby, what kinds of hypocrisy in the film Boss Baby, what were the factors of hypocrisy found in the film Boss Baby, and what were the revelation of main characters self-deception to raise his hypocrisy. The data in this research were in the form of utterances and situations that referred to self-deception and hypocrisy in Boss Baby. This research was done by analyzing the data qualitatively. There were some steps in analyzing the data; identifying, classifying, describing, and analyzing the data. The researchers also used theory of self-deception from Mele, theory of kinds of hypocrisy from Spiegel and theory factors of hypocrisy from Lonnie Lee Best. The findings of the analysis were eleven data found by the researchers; five self-deception, four kinds of hypocrisy (hypocrisy of pretense, hypocrisy of blame, hypocrisy inconsistency and hypocrisy of complacency), a factor of hypocrisy (carnal desires), and a datum of self-deceptionrevelation to raise hypocrisy,the boss baby actually wants a family not a position.